Varying Responses to Heat Stress and Salinization Between Benthic and Pelagic Riverine Microbial Communities - Lisa Boden; Dana Bludau; Guido Sieber; Aman Deep; Daria Baikova; Gwendoline M. David; Una Hadžiomerović; Tom L. Stach; Dominik Buchner; Jens Boenigk (Environmental Microbiology, 2025)
Microbial communities play a crucial role in the functioning of freshwater ecosystems but are continuously threatened by climate change and anthropogenic activities. Elevated temperatures and salinisation are particularly challenging for freshwater habitats, but little is known about how microbial communities respond to the simultaneous exposure to these stressors. Here, we use mesocosm experiments and amplicon sequencing data to investigate the responses of pelagic and benthic microbial communities to temperature and salinity increases, both individually and in combination. Our results highlight the varying responses of freshwater microbial communities, with sediment communities exhibiting greater stability in response to environmental changes compared to water column communities, and salinisation having a more pronounced impact on microeukaryotes compared to prokaryotes. Simultaneous exposure to elevated temperature and salinity reduced the impact of salinisation on prokaryotes, while microeukaryotes were similarly affected by the combined treatments and salinisation alone. These findings emphasise the complexity of microbial responses to single and multiple stressors, underscoring the need to consider both individual and interactive effects when predicting ecosystem responses to environmental changes.